An unconventional full dual-cation battery. (March 2021) - Zhu, Yunpei; Lei, Yongjiu; Liu, Zhixiong; Yuan, Youyou; Alshareef, Husam N.
Abstract: Organic dual-ion batteries show high energy densities which are, in principle, suitable for large-scale energy storage, but they suffer from inherent instability and safety issues. Aqueous batteries feature low cost, high ionic conductivity, and much improved safety, showing more enormous potential for grid-scale energy storage. Conventional dual-ion batteries (DIBs) involve the reversible intercalation of electrolyte-born anions and cations into cathodes and anodes, respectively. Here we develop a new full aqueous battery involving the co-intercalation of K + and H + in both anode and cathode. This dual-ion battery constitutes a cathode of defective Prussian Blue nanostructures, an anode of atomically thin Ti3 C 2 T x MXene nanosheets, and an aqueous electrolyte of mildly acidic KNO3 solution. The open frameworks of both cathode and anode together with the existence of abundant structural water in both electrodes enable fast kinetics for K + and H + (de)intercalation. Accordingly, the full battery exhibits improved energy (e.g., 41.5 Wh kg 1 based on both cathode and anode) and power (e.g., 5030 W kg 1 ) densities, whereas capacity retention of 74% can be achieved after 3000 cycles. We believe that this new dual-cation battery design presents a promising way to improve aqueous battery performance. Graphical Abstract: Different from the conventional dual-ion batteries, a dual-cation battery is developed using a nanostructured Prussian Blue cathode and a Ti3 C2 T x MXene anode. The structural water networks in cathode and anode enable fast co-intercalation of H + and K +, allowing for improved power and energy densities and stability for this dual-cation battery. ga1 Highlights: Abundant structural H2 O in Prussian Blue cathode and MXene anode. Sufficient tunnel size of cathode and interlayer space of anode. Promoted H + and K + cointercalation into cathode and anode induced by structural H2 O and enlarged tunnels/interlayer spacing. Enhanced energy density, power density and cycling stability.